2023
DOI: 10.1055/a-2187-0966
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Pulmonary Embolism: Can We Dismantle the “Obesity Paradox”

Samuel Z. Goldhaber

Abstract: No Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Non-PE-based studies have highlighted that cardiopulmonary fitness is an often-overlooked potential modifier of obesity paradox, and levels of fitness can significantly alter the inverse association between obesity and mortality [21]. The alternative explanation may be that BMI is not be the ideal definition of obesity [22]. In a study from the UK Biobank, waist-hip ratio was found to have the strongest association with all-cause mortality when compared with BMI and fat mass index [23].…”
Section: Discussionmentioning
confidence: 99%
“…Non-PE-based studies have highlighted that cardiopulmonary fitness is an often-overlooked potential modifier of obesity paradox, and levels of fitness can significantly alter the inverse association between obesity and mortality [21]. The alternative explanation may be that BMI is not be the ideal definition of obesity [22]. In a study from the UK Biobank, waist-hip ratio was found to have the strongest association with all-cause mortality when compared with BMI and fat mass index [23].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the study from Gaugler et al 47 reassuringly confirmed that body mass index did not impact the effectiveness of ageadjusted D-dimer in patients suspected of having PE. While weight management may prove beneficial in reducing the burden of VTE, 48 preventing obesity in the first place should become a priority. 49 Certain type of dieting that venous thrombosis patients may be attempting are also associated with potential risks, as illustrated by the particularly intriguing case report, of an individual who developed DVT complication while on a zero-calorie diet regimen.…”
Section: Weightmentioning
confidence: 99%